No evidence of improvements in energy metabolism after 1 week of nitrate and citrulline co-supplementation in elite rowers - Viribay, A.; Alcantara, J. M. A.; López, I.; Mielgo-Ayuso, J.; Castañeda-Babarro, A. (European Journal of Applied Physiology, 2024)
Purpose Citrulline (CIT) and beetroot extract (BR) supplements positively impacts exercise performance in elite rowers. However, its influence on metabolic outcomes such as whole-body volumes of oxygen consumption (VO2) and carbon dioxide production (VCO2), substrate oxidation, energy expenditure (EE), and gross efficiency remains unknown. We studied the effects of 1 week of daily co-supplementation of 3.5 g BR (500 mg NO3-) plus 6 g CIT on VO2 and VCO2 kinetics, substrate utilization, EE, and gross efficiency in elite male rowers compared to a placebo and to a BR supplementation.